Analisis Target Pemasaran Produk Speedy Berdasarkan Motivasi Dan Kompensasi - Tambunan, James Ronald; Sartika, Dewi; Tambunan, Kevin (Journal of Information System, Applied, Management, Accounting and Research, 2022)
PT.Telekomunikasi Indonesia, Tbk. Regional Office of Telecommunications (Kandatel) Field must be able to achieve sales targets of Speedy prime product. In achieving these sales reps needed reliable. Where asset sales reps can be said of an organization in achieving its goals. Therefore, every organization seeks to enhance motivation and a good compensation to the salespeople. Through good compensation, is expected to increase the motivation of salespeople working so that organizational goals can be achieved as planned. Formulation of the problem in this research are: (1). Far the effect of compensation, and salesperson motivation towards achieving sales targets Speedy PT TELKOM, Kandatel Medan, and (2). How to achieve speedy sales before and after the implementation of compensation and motivation of salespeople. The Theory that used in this research is the theory of Human Resource Management (HRM), relating to the theory of compensation and motivation, and theories of Marketing Management, relating to the theory of achievement against sales targets. This study aimed to analyze the effect of compensation and motivation towards the achievement of sales targets Speedy. It also investigated how the speedy attainment of sales before and after the implementation of compensation and motivation to the salespeople. This Research used Quantitative Descriptive Method that is supported by survey, and explanatory. The number of the sample is 61 respondents are salespeople Speedy. The analysis method used is simple regretion to examine the first, and the second test method using comparative analysis. The results of this research show that: (1) Compensation and Motivation has high significant effect to the achievement of high sales targets Speedy. (2) There is a significant difference to the speedy attainment of sales before and after implementation of compensation, and motivation of salespeople. Analysis using a confidence level of 95 percent.